2012
DOI: 10.1186/1475-2875-11-124
|View full text |Cite
|
Sign up to set email alerts
|

A high-throughput method to detect Plasmodium falciparum clones in limiting dilution microplates

Abstract: BackgroundMolecular and cellular studies of Plasmodium falciparum require cloning of parasites by limiting dilution cultivation, typically performed in microplates. The parasite's slow replication rate combined with laborious methods for identification of positive wells has limited these studies. A new high-throughput method for detecting growth without compromising parasite viability is reported.MethodsIn vitro parasite cultivation is associated with extracellular acidification. A survey of fluorescent pH ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 9 publications
1
23
0
Order By: Relevance
“…By identifying gluconate as a nontoxic substitute anion, this study also found that parasites tolerate significant reductions in external Cl − ( EC 50 of 31 mM). Combined with another study showing that the parasite tolerates a broad range of extracellular H + concentrations [79], these studies indicate that the parasite has a significantly greater tolerance of changes in monovalent ion concentrations than cultured mammalian cells. This tolerance parallels that seen with dinoflagellates, to which apicomplexan parasites are closely related [80].…”
Section: Proposed Roles For Increased Permeabilitymentioning
confidence: 83%
“…By identifying gluconate as a nontoxic substitute anion, this study also found that parasites tolerate significant reductions in external Cl − ( EC 50 of 31 mM). Combined with another study showing that the parasite tolerates a broad range of extracellular H + concentrations [79], these studies indicate that the parasite has a significantly greater tolerance of changes in monovalent ion concentrations than cultured mammalian cells. This tolerance parallels that seen with dinoflagellates, to which apicomplexan parasites are closely related [80].…”
Section: Proposed Roles For Increased Permeabilitymentioning
confidence: 83%
“…The transfected culture was selected with 2.5 nM WR99210 and screened for homologous recombination by PCR. Integration into the clag3.1 gene was detected after 6 months; the HB3-c3A1210T clone was generated by limiting dilution (25).…”
Section: Methodsmentioning
confidence: 99%
“…Growth inhibition studies with the HB3 3rec parasite were performed after transport-based selection with ISPA-28, to achieve expression of the chimeric clag3 gene generated through allelic exchange transfection. Limiting-dilution cultures to obtain parasite clones were performed in 96-well microplates; positive wells were detected by using the 5(and 6)-carboxy-seminaphthorhodafluor-1 method (Lyko et al, 2012).…”
Section: Methodsmentioning
confidence: 99%